Comparing the Performance of Value and Growth Strategies;Individual Ratios and Combined Measures - Gholam Hossein Assadi; Saeed Eslami Bidgoli (تحقیقات مالی, 2014)
Investing on growth stocks and value stocks has represented one of the research topics on strategies creating excess return. In this paper, which focuses on companies listed in Tehran Stock Exchange, companies are categorized into growth and value based on certain measures and then their performances are studied. In addition to individual ratios used in a large volume of researches, combined measures are developed by harmonic mean. Also random-weight method is used to form value and growth portfolios. In performance evaluation Sharpe and Sortino ratios are used in this paper in addition to annual returns. In this paper developing combined measures is shown to lead to better performance of the portfolios. Furthermore forming portfolios using random-weight method enables investors to form multiple portfolios.